2014
DOI: 10.1007/s40139-014-0041-3
|View full text |Cite
|
Sign up to set email alerts
|

Danio rerio: Small Fish Making a Big Splash in Leukemia

Abstract: Zebrafish (Danio rerio) are widely used for developmental biology studies. In the past decade, D. rerio have become an important oncology model as well. Leukemia is one type of cancer where zebrafish are particularly valuable. As vertebrates, fish have great anatomic and biologic similarity to humans, including their hematopoietic and immune systems. As an experimental platform, D. rerio offer many advantages that mammalian models lack. These include their ease of genetic manipulation, capacity for imaging, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 103 publications
(169 reference statements)
0
7
0
Order By: Relevance
“…The first transgenic zebrafish leukemia model was created 15 years ago and targeted murine c- Myc ( mMyc ) to thymocytes of AB strain zebrafish, leading to the rapid development of T-cell acute lymphoblastic leukemia (T-ALL) [3]. Additional genetic models were subsequently developed that result in induction of T-ALL [4], but B-cell leukemia models lagged behind [5, 6].…”
mentioning
confidence: 99%
“…The first transgenic zebrafish leukemia model was created 15 years ago and targeted murine c- Myc ( mMyc ) to thymocytes of AB strain zebrafish, leading to the rapid development of T-cell acute lymphoblastic leukemia (T-ALL) [3]. Additional genetic models were subsequently developed that result in induction of T-ALL [4], but B-cell leukemia models lagged behind [5, 6].…”
mentioning
confidence: 99%
“…Not only was this the first transgenic ALL model in D. rerio , but also the first zebrafish cancer model overall. Now, the number of zebrafish T-ALL models has reached double digits, as summarized below [12,13,14,15] (Table 1).…”
Section: Zebrafish Acute Lymphoblastic Leukemia Modelsmentioning
confidence: 99%
“…Few reports of zebrafish B-ALL exist, although differences between D. rerio and human B cells are comparably similar to those between T cells of these species [77]. The many successful zebrafish T-ALL models suggest D. rerio can likely emulate several human B-ALL subtypes, but currently, zebrafish B-ALL models lag behind [13,15]. Here, we will review the three zebrafish B-ALL models reported to date (Table 1), but it is likely many others will soon follow.…”
Section: Zebrafish Acute Lymphoblastic Leukemia Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the fact that zebrafish T-ALL models had proven to be fertile grounds for study, B-ALL modeling in D. rerio had not been fruitful, with only one low penetrance and long latency line reported [54]. This was curious because a zebrafish recombination activating gene 2 (rag2) promoter-active in both immature T and B cells-was used to regulate most of these transgenic oncoproteins in the various T-ALL lines, yet D. rerio B-ALL had not been reported in them [55,56]. Overall, since B-ALL is the more prevalent type in patients, the lack of B-lineage models was particularly unfortunate.…”
Section: Introductionmentioning
confidence: 99%